The Effect of Multiple Intelligences Based Instructional Model on Learning Outcomes IPAS Grade V in 2 Sentul Elementary School - Makantika, Farahdibah Ade; Barus, Yohannes Kurniawan; Muzaki, Ferril Irham (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
The aim of the research is to see the effect of instructional models with multiple intelligences (MI) on the science and science learning outcomes of class V at SDN 2 Sentul. Researchers apply a quantitative approach, with the type of research through experimental research. The experimental group received action in the form of implementing a MI based instructional model in the learning process. And the control group did not receive special actions or apply conventional learning models. The research design applied by the researcher is a quasi experimental design in the form of a non-equivalent control group design research. In these findings, two groups were used, namely, the experimental group and the control group. The sample consisted of 25 students and 27 students in the experimental class. This instrument is in the form of a questionnaire and multiple choice test. The results explain the magnitude of Sig. there is 0.003 < 0.05, so Ho is rejected and Ha is accepted. In accordance with these results, it can be stated that there is an influence of instructional models with multiple intelligences (MI) on the science and science learning outcomes for class V at SDN 2 Sentul.